Figure 2 from: Cripps CL, Eberhardt U, Schütz N, Beker HJ, Evenson VS, Horak E (2019) The genus Hebeloma in the Rocky Mountain Alpine Zone. MycoKeys 46: 1-54. https://doi.org/10.3897/mycokeys.46.32823 - Cripps, Cathy L.; Eberhardt, Ursula; Schütz, Nicole; Beker, Henry J.; Evenson, Vera S.; Horak, Egon (Zenodo, 2019)
Figure 2 ITS overview tree of the genus Hebeloma in Europe from Beker et al. (2016) fig. 12A modified. Grey boxes indicate species clusters represented in separate tree or network figures. Red lines indicate branches with ML bootstrap support of ≥ 80%. # = genus Hebeloma; D = H.sect.Denudata; H = H.sect.Hebeloma; V = H.sect.Velutipes; * = species recorded from the Rocky Mountains. For further details see Beker et al. (2016) and the running text.